Digitalisasi Manajemen Pendidikan Teologi di Era 4.0 Menggunakan Learning Management System Moodle - Vicky Samuel Sutiono; Nunuk Rinukti; Charista Jasmine Siahaya (Sekolah Tinggi Alkitab Jember, 2022)
In the world of education in the last two years has experienced a relatively significant impact due to the Covid 19 pandemic. Teaching and learning activities that are usually carried out face to face currently must be carried out online using various software to continue the teaching and learning process. Theological colleges are also required to think of relevant steps to deal with the current situation. Therefore, it is important to apply a moodle-based Learning Management System (LMS) with the aim of disciplining students, especially in making attendance and collecting assignments that have been set by educators. With the development of the world of education today, students and educators are forced to adapt to the development of the world of education in the field of technology. This writing method is an observation method by looking at the phenomenology of the world of education during the Covid-19 pandemic. The conclusion of this study is that the digitalization of education management in the 4.0 era is very much needed to facilitate the online learning process in universities. AbstrakDunia Pendidikan dalam dua tahun terakhir ini mengalami dampak yang yang relatif signifikan akibat adanya pandemic Covid 19. Kegiatan belajar mengajar yang biasanya dilakukan secara tatap muka saat ini harus dilakukan secara online dengan menggunakan berbagai software untuk tetap dapat melakukan proses belajar mengajar. Perguruan tinggi teologipun dituntut untuk memikirkan Langkah yang relevan untuk menghadapi situasi saat ini. Maka pentingnya diterapkan Learning Management System (LMS) berbasis moodle dengan tujuan untuk lebih mendisiplin peserta didik terutama dalam melakukan presensi, dan pengumpulan tugas yang telah ditetapkan oleh para pendidik. Dengan berkembangnya dunia pendidikan saat ini, peserta didik dan para pendidik dipaksa untuk beradaptasi dengan perkembangan dunia pendidikan di bidang teknologi. Metode penulisan ini adalah metode observasi dengan melihat fenomonologi dunia pendidikan di masa pandemi Covid-19. Kesimpulan dari penelitian ini adalah bahwa digitalisasi manajemen pendidikan di era 4.0 sangat diperlukan untuk mempermudah proses pembelajaran daring di perguruan tinggi.